Identifiying potential biomarkers in the secretome of oral cancer cell lines by comparative proteomic analysis / Chang Hong Yun - Chang, Hong Yun (2013)
Early detection cancer associated biomarker is believed to improve the prognosis outcome of oral cancer by allowing for early treatment. However, discovery of potential oral cancer biomarkers in sera is like looking for a needle in haystack due to the large dynamic range in the concentration of serum protein. Therefore, a study secretome of established cell lines is proposed to bypass such obstacle to discover those secreted biomarkers from tumor mass. Most oral cancer biomarkers discovery researches on secreteome of cell lines lacks normal cell lines as control. In this study, several normal primary cultures (316N, 317N, 322N, 326N) were successfully established without hTERT immortalization. By comparison the proteomes of cancer cell lines (48T, 153T, H400) and normal primary cultures using 2D gel electrophoresis, 31 protein identities were recognized have changed in abundance in the cancer cell lines secretome. Bioinformatic analysis of these proteins showed that all identified proteins were possibly secreted in either a signal dependant pathway or golgi independent pathways. The analysis also demonstrated that their expression dynamics were relevant to cancer progression. A concomitant qPCR validation of selected proteins transcript levels demonstrated that metalloproteinase VII (MMP-7), heterogeneous nuclear ribonucleoprotein A2/B1 (HNRNPA2/B1), peroxiredoxin-1 (PRDX1), tissue inhibitor metalloproteinase-1 (TIMP1), laminin beta 3 (LAMB3), interleukin-1 receptor antagonist (IL1RN), calcium binding protein S100-A8 (S100A8), and Secreted protein, acidic, cysteine-rich (SPARC) were significantly differential expressed (p=0.05) and worthwhile for further investigation. With further studies, these proteins may be developed into potential diagnostic and prognostic marker candidates for oral cancer.